The Treatment of Ipso Facto Clauses in Canada - Ho, Adrienne (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2015)
Whether a debtor is an individual or a sophisticated financial institution, a common issue that arises is whether its insolvency alters the rights of the parties with whom the debtor has entered into contracts. Could the non-defaulting party to the contract, on the basis of the debtor’s insolvency, terminate or amend the contract? Could it demand accelerated payment? Many parties preserve contractual rights, through what are commonly known as ipso facto clauses, to terminate and amend contracts or to demand an accelerated payment in the event that a counterparty to the contract becomes insolvent. Despite recent amendments to the Bankruptcy and Insolvency Act (BIA) and the Companies’ Creditors Arrangement Act (CCAA), the validity of ipso facto clauses, outside the context of derivatives contracts, is an issue that has not been thoroughly addressed in the Canadian literature. This article will trace the anti-deprivation rule in England, culminating in the United Kingdom Supreme Court’s leading case: Belmont Park Investments PTY Ltd. v. BNY Corporate Trustee Services Ltd. and Lehman Brothers Special Financing Inc. It will then explore to what extent recent amendments to the BIA and the CCAA have displaced the common law rule in Canada. Both the BIA and the CCAA have nullified ipso facto clauses in some but not all situations, the most notable exceptions being cases involving corporate bankruptcies and receiverships. This article will conclude with a discussion of the codified exceptions to the common law principles and whether the Canadian jurisprudence might incorporate some of the modifications to the anti-deprivation rule introduced by Lord Collins in Belmont.